MORPHOFUNCTIONAL PECULIARITIES OF MUCOSAL IMMUNITY DEPENDING ON METHODS OF OPPORTUNISTIC MICROBIAL INTRODUCTION - O. V. Lebedinskaya (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Immunophenotypic and morphological peculiarities of immune reactions under intranasal, peroral and subcutaneous introduction of multicomponent vaccine Immunovac VP-4 containing a group of opportunistic bacterial antigens were investigated. The investigated preparation was found to cause marked activation of congenital immunity effectors both in parenteral and mucosal immunization. It is manifested in the expression of differential, costimulatory, adhesive molecules on the surface of mononuclear leukocytes in proliferation of key mucosal immunity effectors (γδТ, В1, NK cells), and changes in structure, cellular composition of immunocompetent organs both regional and distant as to the site of introduction. Currently existing data on effects and mechanisms of vaccine and immunomodulator mucosal introduction allows considering the development of mucosal mono- and associated vaccines as the priority direction in modern vaccinology.